تقييم مواد الحوار في كتاب الحكمة لتعليم اللغة العربية لطلاب الصف العاشر في المدرسة الثانوية الإسلامية الحكومية 2 بكاسي - Muhammad Haidar Al-Hafiizh; Zainal Muttaqin; Fatima El-Zahraa (Penerbit Minhaj Pustaka, 2025)
This study aims to analyze the suitability of teaching modules and evaluate the relevance of Hiwar materials in the Hikmah textbook used for Arabic language instruction among tenth-grade students at MAN 2 Bekasi. The evaluation employs assessment criteria from Idhoat by Abdulrahman bin Ibrahim Al-Fawzan, focusing on the integration of language skills, particularly speaking, and also follows the evaluation standards issued by the Ministry of Religious Affairs of the Republic of Indonesia regarding content suitability. A descriptive qualitative method was applied, using observations, interviews, and documentation as data collection techniques. The findings reveal that the Hiwar materials in the Hikmah textbook only partially meet the established evaluation standards. Therefore, improvements are necessary to enhance the effectiveness of the material. These improvements should not only involve the publisher, but also teachers and schools, in order to develop better teaching strategies and supportive infrastructure for Arabic language education in general, and for teaching Hiwar materials in particular.